Molecular studies of Iranian populations support the morphology-based taxonomic separation of Medicago rigidula and M. rigiduloides - Bayat, Mitra; Assadi, Mostafa; Small, Ernest; Mehregan, Iraj (Phytotaxa, 2021)
A comprehensive study was undertaken to understand the genetic status and help to clarify the division of Medicago rigidula (largely European) and Medicago rigiduloides (largely Asian). Genetic diversity parameters collectively suggested a low genetic diversity (avg. Ho, 0.073; He, 0.374) accompanied by high population differentiation (avg. F, 0.832; Gst, 0.362). Structure analysis divided 71 individuals (14 Iranian populations) into two highly distinct genetic groups (K=2) with significant genetic homogeneity. It also indicated the strong effect of the selfing mating-system as the main reason for the genetic diversity status and population structure. The population grouping was strongly confirmed by various clustering methods. Populations from north and northwestern Iran made up a distinctive genetic group corresponding to M. rigidula while the second group corresponding to M. rigiduloides harboured the western and two of the northwestern populations. The outcomes of this study provide the first reliable molecular evidence supporting the M. rigidula-M. rigiduloides separation previously suggested by morphology.